Letramento matemático e histórias infantis : significações matemáticas em um 2º ano do ensino fundamental - Souza, Talita Fernanda de (2018)
This research is based on a qualitative methodological approach and investigates the mathematical meanings produced by Second Grade students and how they are evidenced when in the Mathematical teaching with children’s stories, in order to answer the research question: “What is the process of mathematical meanings of a Second Grade student in a teaching combining children’s histories and numeracy?”. Through a partnership between the researcher and the teacher of a Second Grade class, children’s histories were used as a pedagogical resource in the Mathematical teaching. Since this proposal was part of the PNAIC of numeracy (BRASIL, 2014), a program dedicated to the training of literacy teachers, we established as a requirement that the partner teacher had been part of such program. The analysis of the student’s mathematical meanings was based on transcriptions of recorded lessons when children’s histories were used as a pedagogical resource; students answers for problematizations based on such histories; and an interview with the partner teacher. For the data analysis, we choose three categories: the first with respect to the mathematical meanings demonstrated by the students in the moments of reading and discussion of the children’s histories; the second refers to the students mathematical meanings when solving problems based on the children's book; and the third category refers to the teacher’s perception of the students learning of Mathematics regarding the children’s histories approach, it’s usage and the partnership. We can highlight that the student’s mathematical meanings are contextually present and they are related to mathematical concepts presents in the children’s histories used for the Mathematical teaching during the research. The students connected mathematical concepts, the histories narrative, and daily and nondaily concepts, evidencing such meanings on reading, problem-solving, and socialization via orality, writing and drawing. We believe that the teacher’s performance during the lessons was essential to produce meanings by the students, serving them as a model for literacy. Moreover, we could observe how a PNAIC proposal was developed in class, bringing up relevant questions about teaching and teacher’s training.